2018
DOI: 10.1111/ajad.12826
|View full text |Cite|
|
Sign up to set email alerts
|

Gender differences in mental health and substance use disorders and related healthcare services utilization

Abstract: Background and Objectives Pathological gambling often co‐occurs with other psychiatric disorders. Gender differences in treatment‐seeking behaviors among patients with pathological gambling diagnosis remain poorly understood. This study assessed gender differences in healthcare services utilization in patients seeking treatment for pathological gambling, substance use, and mental health co‐occurring conditions. Methods Study data were derived from a representative sample of the Massachusetts All Payers Claims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…A significantly greater proportion of probationers in drug courts were female. In line with prior studies, [22][23][24] we found that female probationers used more treatment services than male probationers.…”
Section: Discussionsupporting
confidence: 92%
“…A significantly greater proportion of probationers in drug courts were female. In line with prior studies, [22][23][24] we found that female probationers used more treatment services than male probationers.…”
Section: Discussionsupporting
confidence: 92%
“…Although, gender gaps in health and health-related factors is globally declining [31], it still exists in both developed and developing countries [32]. Females generally experience higher health-related outcomes including mental disorders, and healthcare services utilization [33]. SES of females are generally lower than males (see, for example, a positive value of the C for male in Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, many individuals with SZ avoid getting help, estimates of 20-70% do not seek for help worldwide as shown in previous studies 3 . Many factors in uence whether or not individuals with mental disorders seek-help, such as gender, location of, annual income, type of medical insurance, marriage status, stigma and other social and culture factors [4][5][6][7] . However, research focusing on whether or not individuals with SZ seek help is rare.…”
Section: Introductionmentioning
confidence: 99%